Do government schools improve learning for poor students? Evidence from rural Pakistan. (2nd November 2019) - Aslam, Monazza; Malik, Rabea; Rawal, Shenila; Rose, Pauline; Vignoles, Anna
ABSTRACT: Pakistan's Punjab province has witnessed numerous education reforms in recent years. Many of these reforms have been aimed at improving the well-documented low levels of learning by focusing on improving teaching quality. The rhetoric suggests that government schools, particularly those in rural areas with a more disadvantaged pupil base, are especially ineffective at imparting learning. This paper seeks to investigate whether children in rural Punjab are learning literacy and numeracy over the course of a year, and if so, are some pupils progressing more than others. Using recently collected data, it finds that children in our sample are making progress. Variation in progress is found to be greater within schools rather than across them. The competence and qualifications of a teacher also makes a significant difference to a child's academic progress. The paper further finds differential progress for rich and poor students within schools, suggesting an important role for education policy to put in place targeted support towards those from disadvantaged backgrounds to ensure improvements in their learning keep pace with their peers.